Dependence between mental states and physical training of students - Курилко [Mykola Kurilko], Микола Федорович (Slobozhanskyi Herald of Science and Sport, 2013)
A comparative analysis of the parameters of the level of physical and psychological characteristics of the male-students and the female-students of the first year of the main group is presented here. According to the number of similar psychophysiological states it is evident that the motivations to fail are more prone the girls, and with the motivation to succeed prevails for boys. Motivational pole is not vividly expressed almost equally for both boys and girls. Results of the test exercises indicate the relationship between mental states and physical training. Understanding of the mental conditions and ability to regulate them students allows them to improve efficiency of educational activity, avoid the great number of stressogennykh situations or, at least, soften their influences and settle them with the least losses on your own. From other side, teachers, possessing the proper psychological knowledges and abilities, can more effectively to manage students, their educational activity.